Characteristics of Short-term Sequence Memory of Tone Durations - KANOH, Shin'ichiro; HOSHIMIYA, Nozomu; FUTAMI, Ryoko; YOSHINOBU, Tatsuo (Transactions of Japanese Society for Medical and Biological Engineering, 2009)
The mechanism to encode and store the information on time is essential to uncover the nature of temporal information processing in the sensory, memory and higher-order areas in the brain. In this article, the results of psychophysical experiments on short-term memory of tone durations in auditory sequence were reported. Subjects were requested to recall the durations of all the tones presented serially (sequence) by a telegraph key. The performance of recall was evaluated by correlation coefficients and the distribution in correlation diagram between presented and recalled tone durations, and the relationship to the serial order and the number of tones in a presented sequence were investigated. It was shown that the performance of the recall of tone durations could be evaluated by cross-correlation, and the performance decreased when the serial order of the target tone in the presented sequence was later or the number of tones in a sequence was larger. It was also shown that there were some types of characteristic distribution on the correlation diagram between presented and recalled tone durations which corresponded to the degree of memory decay. This result indicated that the behavioral process of memory decay of the analogue (non-categorized) information could be observed by the profile of correlation diagram.